Cadaver Anatomy Soft Skills Scale (CASSS): Design and preliminary validation of a tool to assess student perceptions of the impact of cadaveric anatomy instruction on soft skills for future healthcare workers - Camryn J. Pierce; Amanda R. Howard; Katelynn M. Corder (BMC Medical Education)
Abstract As technology becomes more advanced, the effectiveness and appropriateness of cadaver dissections has been called into question. In addition to academic effectiveness, cadaver dissection can lead to both positive and negative emotional responses, potentially affecting so-called “soft skills” associated with effective healthcare professionals. In particular, we are interested in the perceived effect of cadaveric dissection on empathy, confidence, and professional boundaries in students who have completed cadaveric dissection-based gross anatomy courses. In this study, we validate a new tool to assess these perceived effects using survey data from graduate students who have completed a graduate level gross anatomy course. This instrument was validated by evaluating convergent and divergent validity of the CASSS established through Pearson’s product moment correlations by correlating obtained factors with self-perceived general empathy, confidence, mortality, and professional boundaries scores. This tool will be useful for determining the impact that various anatomical education techniques have on the development of soft skills (empathy, confidence, and professional boundaries) associated with successful healthcare workers.